Bed capacity and surgical waiting lists: a simulation analysis - Manel Antelo; Francisco Reyes Santias; Adela Martinez Calvo (European Journal of Government and Economics (EJGE), 2015)
Waiting time for elective surgery is a key problem in the current medical world. This paper aims to reproduce, by a Monte Carlo simulation model, the relationship between hospital capacity, inpatient activity, and surgery waiting list size in teaching hospitals. Inpatient activity is simulated by fitting a normal distribution to real inpatient activity data, and the effect of the number of beds on inpatient activity is modelled with a linear regression model. Analysis is performed with data of the University Multi-Hospital Complex of Santiago de Compostela (Santiago de Compostela, Spain), by considering two scenarios regarding the elastiticity of demand with bed increase. If demand does not grow with an increase on bed capacity, small changes lead to drastic reductions in the waiting lists. However, if demand grows as bed capacity does, adding additional capacity merely makes waiting lists worse.
Keywords: 330; Hospital beds; inpatient activity; length of stay; Monte Carlo simulation; surgery waiting lists